Peran Kepala Mis Raudhatul Ulum Pematang Rambai dalam Mengurangi Pekerja Anak Putus Sekolah di Pematang Rambai Kuala Mandor A - Nurhamid Nurhamid (Raheema, 2019)
Every people who legally have Indonesian citizenship identity have a right to gain a better education service. To deal with the children-worker’s problem, an intense and continuous effort is urgently needed. One of the efforts is the cooperation among each institution such as government, social worker, non-government organizational, etc. In MIS Raudhatul Ulum Pematang Rambai, for instance, its headmaster has worked to decrease the number of children workers that lead to being dropout students. Furthermore, the children workers in Pematang Rambai Desa Kuala Mandor A exist because of several factors such as poverty, parents’ education awareness, and low studying interest factor on children. Moreover, the children have merely an enthusiasm for working instead of studying. Parents, actually, should provide enough time for children to develop their talents and interests. Therefore, the large number of dropout students caused by working has become a trigger for the headmaster of MIS Raudhatul Ulum to decrease the children workers.